PENGARUH DESAIN INTERIOR, BRAND IMAGE, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN TAMU MENGINAP DI MAILAKU GUEST HOUSE - Kadek Dwi Candra Kirani; Daniel Manek (Jurnal Bakti Saraswati (JBS), 2024)
The decision to stay can arise when the hotel is felt to be able to provide a sense of satisfaction and comfort guests while staying at a hotel. The factors that influence the decision to stay are interior design, brand image and quality of service on the decision of guests to stay at Mailaku Guest House. The population in this study is prospective guests or guests who have stayed at Mailaku Guest House totaling 160 people. The sample used in this study is purposive sampling because it uses several appropriate criteria and has been determined by the author. The method in this study used observation, interviews and questionnaires. This study used SPSS version 26. The results in this study show that partially interior design variables have a positive and significant effect on guests' decision to stay, brand image variables have a positive and significant effect on guests' decision to stay and service quality variables have a positive and significant effect on guests' decision to stay. The variables of interior design, brand image and service quality together affect the decision of guests to stay.